2018
DOI: 10.1016/j.mtla.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solidification induced composition gradients on carbide precipitation in FeNiCr heat resistant steels

Abstract: Secondary precipitation of Cr-rich carbides in heat resistant austenitic stainless steels has been investigated both experimentally and using finite element simulations. The microstructural evolutions in two commercial grades were characterized using electron microscopy. A special emphasis was given on the peculiar spatial distribution of M23C6 secondary carbides exhibiting precipitate free zones surrounding primary carbides, and high density precipitate zones extending with longer aging times. Solidification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…Appearance and dissolution of this phase during ageing or creep can be explained as follows. As shown by Roussel et al [28], depletion in Cr and enrichment in Ni at the primary Cr-carbide/matrix interface after solidification (Figure 12). The presence of these chemical gradients at the matrix/carbide interface after solidification can act as an additional driving force for the heterogeneous nucleation of the NiAl phase.…”
Section: As-cast Microstructuresupporting
confidence: 56%
See 2 more Smart Citations
“…Appearance and dissolution of this phase during ageing or creep can be explained as follows. As shown by Roussel et al [28], depletion in Cr and enrichment in Ni at the primary Cr-carbide/matrix interface after solidification (Figure 12). The presence of these chemical gradients at the matrix/carbide interface after solidification can act as an additional driving force for the heterogeneous nucleation of the NiAl phase.…”
Section: As-cast Microstructuresupporting
confidence: 56%
“…In good agreement with the phase diagrams of Figure 5, only MC (bright contrast) and M23C6 carbides (darkest phase) are observed in alloys 1, 2 and 5 (Figure 6a, Figure 6b and Figure 6e respectively). Two types of M23C6 carbides are present: coarse M23C6 carbides originating from the transformation of the primary M7C3 carbides and finely dispersed secondary carbides M23C6 resulting from the release of C in the matrix during the transformation of M7C3 into M23C6 [26,28]. In alloys 3 and 4 (Figure 6c and Figure 6d respectively), an additional phase in light grey contrast is observed.…”
Section: As-cast Microstructurementioning
confidence: 98%
See 1 more Smart Citation
“…The coupling with an evolving diffusion profile from the outside to dynamically modify the driving force of precipitation is, on the other hand, rarely encountered. Such coupling has already been proposed in steels [23,24] and aluminium [25], but never in Ti64 to model the precipitation during debinding/sintering processes. In this paper, we evaluate the effect of the debinding conditions (temperature, holding time, heating rate, atmosphere) on both microstructural and mechanical properties of Ti64 scaffolds obtained by DIW.…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of research papers have reported that the distribution, size, amount, morphology, and type of carbide phase all have a great influence on the properties of the alloy [15][16][17][18]. Some researchers have found that the element concentration, element type, element ratio, heat treatment temperature, time, and other factors all have influence on the precipitation of the carbide phase [19][20][21][22][23], however, in essence, carbide is formed by element diffusion, while carbide formation needs the required metal element and carbon element reach the necessary element concentration for carbide formation, which rely on element diffusion [24][25][26][27][28][29]. Some researchers have shown that Si has an effect on the precipitation rate of alloy and can delay the transformation from ε/ε'-carbides to cementite [30,31].…”
Section: Introductionmentioning
confidence: 99%